Development and characterization of nanoemulsions for ophthalmic applications: role of cationic surfactants - Fernandes, Ana R. (2021)
The eye is a very complex organ comprising several physiological and physical barriers that compromise drug absorption into deeper layers. Nanoemulsions are promising delivery systems to be used in ocular drug delivery due to their innumerous advantages, such as high retention time onto the site of application and the modified release profile of loaded drugs, thereby contributing to increasing the bioavailability of drugs for the treatment of eye diseases, in particular those affecting the posterior segment. In this review, we address the main factors that govern the development of a suitable nanoemulsion formulation for eye administration to increase the patient’s compliance to the treatment. Appropriate lipid composition and type of surfactants (with a special emphasis on cationic compounds) are discussed, together with manufacturing techniques and characterization methods that are instrumental for the development of appropriate ophthalmic nanoemulsions.